COVID-19: Navigating Inclusive Recovery towards the New Normal - Mendoza, Ronald U (Archīum Ateneo, 2020)
There are two forms of contagion associated with COVID-19—one related to the virus, and the other to the economic slowdown it has triggered. This paper outlines a framework to better understand the different phases of COVID-19 crisis response, spanning relief, recovery and the possible “new normal”; and it elaborates on the balancing act between economic and health policies. Drawing on a review of international and Philippine policy responses across these different stages, this paper contributes to the crisis response literature by developing a proposal to use the Philippine healthcare sector as a lynchpin of more inclusive and stable economic recovery. Better healthcare and crisis response systems could effectively contain the virus, while also minimizing the economic costs. Emerging evidence suggests that countries with adequate and more inclusive healthcare and social protection systems did not need to resort to draconian crisis contagion measures. What is needed are robust investments that build stronger inclusiveness and coverage by a country’s health system, and enable this to rapidly re-align and ramp up absorptive capacities during a crisis should the need arise.